Newman’s Error Analysis on Junior High School Students’ Mathematical Problem-Solving Ability in the Pythagorean Theorem - Ghefira, Aisyah Muthia; Jupri, Al (Universitas Wiralodra, 2025)
This study aims to identify students’ errors in mathematical problem-solving based on Newman’s Error Analysis (NEA) framework through a qualitative descriptive method. The subjects were 27 eighth-grade students of SMP Negeri 10 Palembang, selected as one intact class to represent common student errors in the learning process. Data were collected using a problem-solving test on the Pythagorean Theorem and interviews, with instruments tested for validity, reliability, difficulty level, and item discrimination. The focus on the Pythagorean Theorem is crucial as it is a foundational topic in junior high school mathematics that supports students’ understanding of geometry, logical reasoning, and higher-level problem-solving. The results show that the most frequent errors occurred in developing solution plans and rechecking answers, while dominant errors in NEA categories were transformation, process skills, and encoding. These findings highlight students’ difficulties in fully understanding problem-solving procedures and provide valuable insights for teachers to design more targeted learning strategies. Practical recommendations include emphasizing problem comprehension, strengthening basic calculation skills, guiding students in problem transformation, and fostering reflective practices such as self-checking, which can help reduce errors and enhance students’ conceptual understanding of mathematics.